Roman Transport Network Connectivity and Economic Integration - Matthias Flückiger; Erik Hornung; Mario Larch; Markus Ludwig; Allard W. Mees (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We show that the creation of the first integrated multi-modal pan-European transport network during Roman times influences economic integration over two millennia. Drawing on spatially highly disaggregated data on excavated Roman ceramics, we document that contemporary interregional trade was influenced by connectivity within the network. Today, these connectivity differentials continue to influence integration as approximated by cross-regional firm investment behaviour. Continuity is partly explained by selective infrastructure routing and cultural integration due to bilateral convergence in preferences and values. We show that our results are Roman-connectivity specific and do not reflect pre-existing patterns of exchange using pre-Roman trade data.
Keywords: F14; F15; F21; N73; R12; R40; O18; 330; Economic integration; Roman trade; transport network connectivity; business links; cultural similarity